Remote teaching during the covid-19 pandemic: challenges, learning and expectation of university professors of Physical Education (Research, Society and Development, 2020)
This research aimed to identify the challenges and the learning of university professors of Physical Education related to remote education during the pandemic of the covid-19, as well as expectations regarding post-pandemic education, through a focus group with university professors from private institutions. The professors witnessed several challenges and learning related to remote teaching. Regarding learning, they highlighted: processes of adaptation, discovery, experimentation and use of new technological tools and new methodological strategies; new ways of relating to students; collaboration with colleagues and pedagogical coordination; and the transfer of experiences from other fields of activity to Higher Education. Professors also stated that they intend to integrate technologies more into teaching in the post-pandemic period. The social detachment caused by the Covid-19 pandemic and emergency remote education has enhanced the development of professors, providing new professional learning opportunities.